Efektivitas Kebijakan Fiskal dan Moneter dalam Mendorong Pertumbuhan Ekonomi di Indonesia - S, Suripto (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Sustainable economic growth will have an impact on improving people's welfare. With high economic growth will reduce unemployment and ultimately improve people's lives. This research will examine the impact of fiscal policy and monetary policy in Indonesia on economic growth.